Turkish Origin Migrants and Their Descendants Hyphenated Identities in Transnational Space Conclusion - Kaya, Ayhan (Palgrave, 2019)
This chapter gives a summary of the main findings of the book. The book concludes that the principal source of the tensions between native and migrant, or minority, communities in modern times stems from essentialist definitions of culture, nation, civilization, religion and citizenship, which are likely to interpellate social-economic realities in a way that culturalizes what is social, political and economic. This book also concludes that state actors of both sending and receiving countries are decisive in the construction of these discursive frames, which have apparently led to the misrecognition, misinterpretation and misdiagnosis of everyday life practices and constraints on migrants and their descendants in general and Euro-Turks in particular.
Keywords: Culturalization; Religiosity; Ideology; Neoliberalism; Deindustrialization